Comparative study to assess the outcome of omitting bladder flap formation from caesarean delivery - Gupta, Pratiksha; Kumari, Suman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of this study is to evaluate the effects of omitting the step of bladder ﬂap formation at lower-segment caesarean delivery. Methods: It is a RCT (randomised control trial), non-blinded study conducted in a tertiary care hospital. A total of 104 women who underwent caesarean delivery (elective or emergency) were prospectively randomized to one of the two groups. In the study group (n= 54), caesarean was performed without formation of a bladder ﬂap. In the control group (n=50), caesarean was performed with the formation of a bladder ﬂap before the uterine incision. Results: There were differences of median skin incision to delivery interval (5 versus 6.5 minutes, P <0.0001), median total operating time (35 versus 44.5 minutes, P 0.0002), and median blood loss (haemoglobin 0.5 versus 1g/dl, P 0.0001) in favor of the study group. Postoperative incidence of urinary tract infection was reduced in the study group (1% versus 9%, P <0.0006) and bowel function returned early in the study group (day 2 versus 3, P<0.0001). Bladder flap formation step was successfully omitted in (11/18, 61.11%) of previous CS (caesarean section) patients in the study group and (7/12, 58.33%) in control group illustrating that unless required, BF (bladder flap) formation step can even be omitted in previous CS patients. Conclusions: Omission of the bladder ﬂap provides short term advantages such as reduction of total operating time, incision-delivery interval, and reduced blood loss and that this technique can even be applied in previous caesarean section patients.